Biodegradable films from poly (lactic acid) (PLA)-chitosan-polyethylene glycol (PEG) : fabrication and evaluation of mechanical properties - Nisham Asmeer, Roslan (2013)
In this research, the production of biodegradable plastic food packaging from biopolymers poly (lactic acid) (PLA), chitosan and polyethylene glycol (PEG) was investigated. In addition, the objective for this research also wants to study the mechanical properties of biofilms at different percentage of weight of polylactic acid, chitosan, and polyethylene glycol (PEG). The biodegradable plastic food packaging was prepared by blending the films based on these four main chemicals (PLA, chitosan, PEG) and 30 ml of silver nanopaticles for every blend of biofilms. Then tested the films with universal testing machine according to American Standard Test Method (ASTM D882) to investigate the mechanical properties (tensile and elongation) with 1 mm thickness film. Then, the mechanical properties of biodegradable food packaging films optimized by changing the parameters of percentage polyethylene glycol (PEG) and ratio of chitosan to PLA using Response Surface Method (RSM) in order to obtain the good biodegradable food packaging films. Degradation rate test has been determined by using the soil burial degradation rate method by burial the blend films for 14 days. The results show that, at the optimum condition, the tensile strength reached the maximum value of 10.573 MPa when the PEG is 17.6 % and PLA is 71.21%. For the elongation at break point, the optimum condition for the elongation at the break point reached the maximum value of 68% when the PEG is 22.07% and PLA is 50%. For the biodegradation rate indicate that the highest value of the chitosan will have the highest degradation rate among the prepared biofilms. As a conclusion the blend films produces will have a good mechanical properties that and can degraded easily.